Model based analysis of piezoelectric transformers - Hemsel, Tobias; Priya, S (Ultrasonics)
Piezoelectric transformers are increasingly getting popular in the electrical devices owing to several advantages such as small size, high efficiency, no electromagnetic noise and non-flammable. In addition to the conventional applications such as ballast for back light inverter in notebook computers, camera flash, and fuel ignition several new applications have emerged such as AC/DC converter, battery charger and automobile lighting. These new applications demand high power density and wide range of voltage gain. Currently, the transformer power density is limited to $40 W/cm{^3}$ obtained at low voltage gain. The purpose of this study was to investigate a transformer design that has the potential of providing higher power density and wider range of voltage gain. The new transformer design utilizes radial mode both at the input and output port and has the unidirectional polarization in the ceramics. This design was found to provide 30 W power with an efficiency of 98% and 30 $\,^{°}$C temperature rise from the room temperature. An electro-mechanical equivalent circuit model was developed to describe the characteristics of the piezoelectric transformer. The model was found to successfully predict the characteristics of the transformer. Excellent matching was found between the computed and experimental results. The results of this study will allow to deterministically design unipoled piezoelectric transformers with specified performance. It is expected that in near future the unipoled transformer will gain significant importance in various electrical components.
Keywords: Piezoelectric transformers

Focusing cross-fire applicator for ultrasonic hyperthermia of tumors - Lierke, E.G.; Hemsel, Tobias (Ultrasonics)
An improved concept for ultrasonic hyperthermia of tumors is presented. This concept is based on past experience of a German government supported project [1], which ended in 1984. It offers a low cost alternative to common RF- and microwave methods for hyperthermia of tumors with volumes between 1 and 40 ml at treatment times between 30 and 60 min. Our new version of the system considerably improves the temperature suppression in the healthy tissue around the target area and enables the adjustment of the beam width to the actual tumor size and the field geometry to the depth and shape of the tumor. The applicator can be used for moderate hyperthermia with tissue overheating up to 10 K or for ablation therapy with short high temperature pulses. Its central area is free for the integration of a commercial ultrasonic diagnostic sector scanner or a Doppler flow sensor in order to support the adjustment of the transducer and to monitor the whole area during the therapy.
Keywords: Moderate hyperthermia

Synergetic driving concepts for bundled miniature ultrasonic linear motors - Mracek, Maik; Hemsel, Tobias (Ultrasonics)
Rotary ultrasonic motors have found broad industrial application in camera lens drives and other systems. Linear ultrasonic motors in contrast have only found limited applications. The main reason for the limited range of application of these very attractive devices seems to be their small force and power range. Attempts to build linear ultrasonic motors for high forces and high power applications have not been truly successful yet. To achieve larger force and higher power, multiple miniaturized motors can be combined. This approach, however, is not as simple as it appears at first glance. The electromechanical behaviour of the individual motors differs slightly due to manufacturing and assembly tolerances. The individual motor characteristics are strongly dependent on the driving parameters (frequency, voltage, temperature, pre-stress, etc.) and the driven load and the collective behaviour of the swarm of motors is not just the linear superposition of the individual drive's forces. Thus, the bundle of motors has to be synchronized and controlled appropriately in order to obtain an optimized drive that is not oversized and costly. We have investigated driving and control strategies of a set of linear ultrasonic motors. Our contribution will be divided into three main parts. In part I ultrasonic linear motors will be introduced. In part II driving strategies for a single motor as well as for a bundle of motors will be presented. These concepts will be verified by simulation results and experimental data. In part III a simplified model for the motor's electromechanical behaviour will be given.
Keywords: Ultrasonic linear motor

Mischbauweise sorgt für frischen Wind - Meschut, Gerson (Konstruktion)

Lipirea în combinatie cu îmbinarile obtinute prin deformare - Hahn, O.; Koyro, M.; Meschut, Gerson (sudura)

Hybridfügen – Grundlagen, Technologie, Anwendungen - Meschut, Gerson (DVM-Bericht 668)

Medienbildung und Gesellschaft

Survey of the present state of the art of piezoelectric linear motors - Hemsel, Tobias; Wallaschek, Jörg (Ultrasonics)
Piezoelectric ultrasonic motors have been investigated for several years and have already found their first practical applications. Their key feature is that they are able to produce a high thrust force related to their volume. Beside rotary drives like the travelling wave motor, linear drives have also been developed, but only a few are presently commercially available. In the present paper, we first describe the state of the art of linear piezoelectric motors. The motors are characterized with respect to their no-load velocity, maximum thrust force, efficiency and other technical properties. In the second part, we present a new motor, which is judged to be capable of surpassing the characteristics of other piezoelectric motors because of its unique design which allows the piezoelectric drive elements to be pre-stressed in the direction of their polarization. The piezoelectric elements convert energy using the longitudinal d33 effect which allows an improved reliability, large vibration amplitudes and excellent piezoelectric coupling. Energy loss by vibration damping is minimized, and the efficiency can be improved significantly. Experimental results show that the motor characteristics can be optimized for a particular task by choosing the appropriate operating parameters such as exciting voltage, exciting frequency and normal force.
Keywords: Linear motor

Eine quasistationäre Meßmethode zur Ermittlung der Wärmeleitfähigkeit polymerer Zwischenschichten in Abhängigkeit von der Temperatur - Koyro, M.; Meschut, Gerson (Tagungsband zur Veranstaltung Werkstoffprüfung 1999)

Normal forms for linear Hamiltonian vector fields commuting with the action of a compact Lie group - Melbourne, Ian; Dellnitz, Michael (Mathematical Proceedings of the Cambridge Philosophical Society)
Abstract We obtain normal forms for infinitesimally symplectic matrices (or linear Hamiltonian vector fields) that commute with the symplectic action of a compact Lie group of symmetries. In doing so we extend Williamson's theorem on normal forms when there is no symmetry present. Using standard representation-theoretic results the symmetry can be factored out and we reduce to finding normal forms over a real division ring. There are three real division rings consisting of the real, complex and quaternionic numbers. Of these, only the real case is covered in Williamson's original work.